Methanolic Moringa oleifera leaf extract protects against epithelial barrier damage and enteric bacterial translocation in intestinal I/R: Possible role of caspase 3 - O A. Afolabi; T M. Akhigbe; T M. Akhigbe; R E. Akhigbe; R E. Akhigbe; B A. Alabi; O T. Gbolagun; M E. Taiwo; O O. Fakeye; E O. Yusuf (Frontiers Media S.A., 2022)
Background: Activation of caspase 3 has been implicated in the pathogenesis of I/R injury in various organs, but there is a paucity of data on its role in IIRI. Also, no reports were found on the beneficial role of methanolic Moringa oleifera leaf extract (MMOLE) in IIRI. This study investigated the involvement of caspase 3 in IIRI, and the impact of MMOLE in IIRI.Methods: Male Wistar rats were randomized into five groups; the sham-operated group that was sham-operated and received 0.5 ml of distilled water for 7 days prior to sham surgery, and the IIRI, febuxostat (FEB) +IIRI, low dose MMOLE (LDMO)+IIRI, and high dose MMOLE (HDMO)+IIRI groups that underwent I/R and also received 0.5 ml of distilled water, 10 mg/kg of febuxostat, 200 mg/kg of MMOLE, and 400 mg/kg of MMOLE respectively for 7 days prior to I/R. Markers of hepatic function, oxidative stress, and inflammation as well as enteric bacterial translocation and histoarchitecture integrity of intestinal and hepatic tissues were evaluated. The bioactive components of MMOLE were also determined by GC-MS.Results: As revealed by GC-MS, the active bioactive components of MMOLE were thiosemicarbazone, hydrazine, 1,3-dioxolane, octanoic acid, 1,3-benzenediamine, 9-octadecenoic acid, oleic acid, nonadecanoic acid, 3-undecanone, phosphonic acid, and cyclopentanecarboxylic acid. MMOLE alleviated IIRI-induced rise in intestinal and hepatic injury markers, malondialdehyde, TNF-α, IL-6, and myeloperoxidase activities. MMOLE improved IIRI-induced suppression of reduced glutathione, thiol and non-thiol proteins, and superoxide dismutase, catalase and glutathione peroxidase activities. These were associated with suppression of IIRI-induced caspase 3 activity and bacterial translocation. Histopathological evaluation revealed that MMOLE attenuated IIRI-induced alterations in intestinal and hepatic histoarchitecture integrity. MMOLE also militated against increased absolute and relative intestinal and hepatic weight, intestinal and hepatic injuries, epithelial mucosal barrier dysfunction, and enteric bacterial translocation associated with IIRI by downregulating oxidative stress-mediated activation of caspase 3.Conclusion: IIRI is associated with a rise in caspase 3 activity. Also, MMOLE confers protection against IIRI, possibly due to its constituent bioactive molecules, especially hydrazine, 9-octadecenoic acid, 1,3-dioxolane, oleic acid, and nonadecanoic acid.